Environmental baselines and reconstruction of Atlantic Water inflow in Bjørnøyrenna, SW Barents Sea, since 1800 CE. (December 2017) - Dijkstra, Noortje; Junttila, Juho; Aagaard-Sørensen, Steffen
Abstract: Metal concentrations, sediment properties and benthic foraminiferal assemblages were investigated in sediment cores in the SW Barents Sea, to reconstruct environmental baselines and natural variability of Atlantic Water inflow since 1800 CE. Metal concentrations correspond to no effect levels and do not influence the foraminifera. Increased Hg and Pb was linked to inflow of Atlantic Water. The data set is considered to reflect the pre-impacted environmental baseline and range in natural variability of the study area. The foraminiferal assemblages in the SW part of the study area showed warming and presence of Atlantic Water towards 1900 CE. The NE part of the region indicate presence of cold Artic Water influenced conditions. Between 1900 and 1980 CE, the SW region indicates reduced inflow of Atlantic Water. From 1980 CE towards the present the assemblages of the entire study area show warming of Atlantic Water and northward retreat of the Arctic Front. Highlights: Natural variability and Atlantic water inflow into the Barents Sea was investigated. Metal concentrations correspond to no effect levels. Foraminifera show presence of Atlantic water around termination of Little Ice age. Atlantic water inflow was reduced between 1900 and 1980 CE Benthic foraminiferal assemblages show enhanced Atlantic water inflow after 1980 CE